Product Variety and Economic Growth - Empirical Evidence for the OECD Countries - Michael Funke; Ralf Ruhwedel (Center for Economic Studies and ifo Institute (CESifo), 2000)
Utilizing panel data for 19 OECD countries we find suppor t for the hypothesis that a greater degree of product variety relative to the US helps to explain relative per capita GDP levels. The empirical work relies upon some direct measures of product variety calculated from 6-digit OECD export and import data. A lthough the issue is still far from being settled, the merging conclusion is that the index of relative product variety across countries is significantly correlated with relative per capita income levels.
Keywords: C23; F41; F43; 330; Product variety; economic growth; panel data; OECD countries